The Acquisition of Indonesian Affixation on Inflection and Derivation of Two to Five Year Old Children - Anindita, Widyashanti Kunthara (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
This study is aimed to reveal affixation both on inflection and derivation and its morphological process, and the phonological process whether children are able to utter every word correctly. The data of this study were utterances taken from two to five year old children at Dharma Wanita Day Care of Central Java Province. The data were collected with observation and conversation methods. The observation method was performed with recording and non-participant observation. Meanwhile, conversation method was performed with elicitation technique. The data were analyzed with distributional method. The results of the analysis are as follows. Firstly, each inflection and derivation has standard and non standard Indonesian affixes. Secondly, both in inflection and derivation, there are deviations of affixations found in the utterances of two to five year old children. Thirdly, there are phenomena in terms of morphological process both in inflection and derivation.